Effect of intracellular carbohydrates on heat resistance of Dictyostelium discoideum spores. - Emyanitoff, R G (1979)
The effect of intracellular trehalose and glycogen on the survival of spores of Dictyostelium discoideum ATCC 25697 after exposure to supraoptimal temperatures was examined. Cells metabolically perturbed by incubation in glucose and inorganic phosphate have intracellular trehalose and glycogen concentrations fivefold and twofold higher, respectively, than those of the controls. These cells were more resistant to the lethal effects of wet heat (45 degrees to 55 degrees C) than were control cells. The presence of 40 mM trehalose in the buffer during heat stress increased the survival of nonperturbed cells to approximately the level of the perturbed cells. No protection was observed when cells were heated in the presence of exogenous glycogen. Glucose or disaccharides other than trehalose when present during heat stress, had no effect on heat resistance. Nonperturbed cells preincubated in 40 mM trehalose and washed before heat stress were more resistant to killing than were controls. Cells perturbed with inorganic phosphate, which has been shown to increase trehalose concentrations but decrease glycogen concentrations, were also more resistant to the lethal effects of wet heat than were controls. The data suggest that trehalose has an effect on the wet-heat resistance of D. discoideum. Some possible mechanisms are suggested.